2013
DOI: 10.1038/sc.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Early low-frequency stimulation of the pudendal nerve can inhibit detrusor overactivity and delay progress of bladder fibrosis in dogs with spinal cord injuries

Abstract: Objectives: To determine the inhibitory effects of pudendal nerve stimulation (5 Hz) on bladder overactivity at the early stage of spinal cord injury (SCI) in dogs, and to explore the possible effects on delayed progression of bladder fibrosis after SCI. Methods: The study was performed using six dogs with spinal cord transection at the T9-T10 level. Group 1 (three dogs) underwent low-frequency electrical stimulation of the pudendal nerve 1 day after spinal cord transection. Group 2 (three dogs) underwent only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Management of SCI‐induced urinary incontinence has always been focused on dealing with a chronic condition rather than attempting to harness its development . Recent studies, however, suggest that early interventions are of clear benefit for SCI patients whether they aim to reduce pain and spasticity or improve bladder function . Accordingly, here we found that early intravesical RTX administration significantly attenuated NDO development, acting in peripheral structures without effects on spinal afferent terminations.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Management of SCI‐induced urinary incontinence has always been focused on dealing with a chronic condition rather than attempting to harness its development . Recent studies, however, suggest that early interventions are of clear benefit for SCI patients whether they aim to reduce pain and spasticity or improve bladder function . Accordingly, here we found that early intravesical RTX administration significantly attenuated NDO development, acting in peripheral structures without effects on spinal afferent terminations.…”
Section: Discussionmentioning
confidence: 49%
“…Altogether, results presented support the benefits of early intravesical administration of RTX to attenuate NDO development. Our data adds to the growing body of evidence that postulates that the anticipation of therapeutic intervention might avoid degradation of bladder function, with a clear positive impact on the SCT patients’ quality of life.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Li et al [6] compared urodynamic parameters measured at 1 and 3 months after T9-T10 surgical SCT in 2 distinct groups of beagle dogs. One group of 3 SCT dogs was subjected to early low-frequency PNS, while the second group of 3 SCT was controls.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, after acute supra-sacral SCI, early pudendal nerve stimulation (PNS) and sacral neuromodulation (SNM) have been reported to successfully obviate DO, enhancing the potential of preventive measures against SCI-related DO [6,7]. …”
Section: Introductionmentioning
confidence: 99%